Recent trends in cesarean section reduction in extreme south of Brazil: a reality only in the public sector? - Marmitt,Luana Patrícia (2022)
Abstract This study aimed to describe changes in cesarean section (C-section) prevalence from 2007 to 2019, in public and private sectors, according to maternal characteristics. We included all puerperal women who gave birth in Rio Grande, Rio Grande do Sul, Brazil, at years 2007, 2010, 2013, 2016 and 2019. A questionnaire was applied up to 48 hours after delivery. We assessed C-section rates over time and described the prevalence according to independent variables. Poisson regression was used. A total of 12.415 puerperal women were included. The prevalence of C-section increased between 2007-2013 (from 51.2% to 61.2%) and decreased between 2013-2019 (48.9% in 2019). This decrease was observed only in the public sector and was higher among the youngest (-10.0 percentual points) and high educated women (-10.3 percentual points). While in the private sector C-section occurrence increased even more (95.7% in 2019). In the public sector, women that were older, with a partner, primiparous, who performed prenatal care in the private system and with adequate prenatal assistance presented higher prevalence of C-section. In the private sector the prevalence was high independently of the maternal characteristics. In order to reduce C-section rates, efficient delivery care policies mainly focused on the private sector are necessary.